Scaling Effects in Sodium Zirconium Silicate Phosphate (Na1+xZr2SixP3−xO12) Ion‐Conducting Thin Films. Issue 8 (4th May 2016) - Ihlefeld, Jon F.; Gurniak, Emily; Jones, Brad H.; Wheeler, David R.; Rodriguez, Mark A.; McDaniel, Anthony H.
Abstract : Preparation of sodium zirconium silicate phosphate (NaSICon), Na1+ x Zr2 Si x P3− x O12 (0.25 ≤  x  ≤ 1.0), thin films has been investigated via a chemical solution approach on platinized silicon substrates. Increasing the silicon content resulted in a reduction in the crystallite size and a reduction in the measured ionic conductivity. Processing temperature was also found to affect microstructure and ionic conductivity with higher processing temperatures resulting in larger crystallite sizes and higher ionic conductivities. The highest room temperature sodium ion conductivity was measured for an x  = 0.25 composition at 2.3 × 10 −5  S/cm. The decreasing ionic conductivity trends with increasing silicon content and decreasing processing temperature are consistent with grain boundary and defect scattering of conducting ions.